Enhanced Expression of Markers for Astrocytes in the Brain of a Line of GFAP-TK Transgenic Mice - Zhang, Xiaoqin; Wang, Dongpi; Pan, Hongyu; Sun, Binggui (Frontiers in Neuroscience, 2017)
GFAP-TK mice are widely used in studies on neurogenesis and reactive astrocytes. Previous studies reported that GCV treatment in GFAP-TK mice resulted in reduced neurogenesis and deletion of proliferating GFAP-expressing astrocytes without affecting mature GFAP-expressing astrocytes. In the present study, we found that GFAP- and vimentin-expressing astrocytes were dramatically increased in the cortex and hippocampus with or without GCV treatment in a line of GFAP-TK mice (Jackson Laboratory, Stock No. 005698), while the neurons and microglia were not affected. In a second line of GFAP-TK mice (MMRRC, Stock No. 037351-UNC) generated in Dr. Heather Cameron’s laboratory in NIH, however, no difference in GFAP and vimentin expression was found in both hippocampus and cortex, regardless of GCV treatment or not. Furthermore, enhanced expression of aquaporin 4 (AQP4) was found in the cortex and hippocampus of the GFAP-TK mice from Jackson lab but not in the brain of GFAP-TK mice from NIH. Our data suggested that we should be careful to select different lines of GFAP-TK mice to study adult neurogenesis or reactive astrocytes.